Reading Between the Headlines : Framing Analysis of Ideological Influences in Pride Coverage by Two American News Outlets - Noukka, Sofia (My University, 2025)
This thesis examines how the headlines of Fox News and ABC News frame the Pride movement. Since these news outlets have distinct political ideologies, conservatism for Fox News and liberalism for ABC News, this thesis also aims to explore how the framing choices reflect each platform’s leanings. As a framework, this study applies Framing Theory popularised by Erving Goffman. The primary material consists of 149 headlines from Fox News and 57 headlines from ABC News that have the keyword “Pride” in relation to the LGBTQ+ movement. These headlines are classified into one of the seven identified framing categories, which are Controversy, Opposition, Policy, Commerce, Culture, Safety, and Support. The categorisation results show that Fox News has a strong emphasis on the Controversy frame, while ABC News provides a more balanced coverage between the categories. Moreover, this study suggests that the influence of the current ideologies of each platform are visible in their headline framing of Pride. This slant is apparent not only in the categorisation results but also in the closer examination of the headline contents. Therefore, this thesis concludes that headline framing can reflect the news outlet’s political ideology and possibly also influence readers’ perceptions of social issues like Pride.
Keywords: framing theory, news headlines, pride movement, LGBTQ+ representation, political ideology